Soft and flexible sensor array using carbon black pillars for object recognition via pressure mapping. (15th July 2020) - Yellapantula, Kartik; Devaraj, Harish; Assadian, Mahtab; Stuart, Logan; Lo, Cheng-Yao; Gan, Wee Chen; Aw, Kean
Highlights: A flexible tactile force sensor array made from carbon black/elastomer pillars. Carbon black/elastomer pillars allows more sensing elements per unit area. Force/pressure map can be derived from sensor array. Abstract: Soft and flexible arrays of pressure or force sensors are particularly useful for wearable and robotic applications. This article presents a soft and flexible sensor array made from carbon black composite pillars. These pillars allows more sensing elements to be constructed in a given planar area. A prototype sensor consisting of a 3 × 3 array of carbon black composite pillars is used to demonstrate their potential. Each pillar shows a reliable corresponding change in resistance with instantaneous pressure or force applied on it. With a sensor array, the pressure distribution across the contact surface of the sensor can be represented as a pressure map allowing the recognition of the shape of an object applying the pressure on the sensor array. The soft and flexible nature of the sensor array allows it to be easily deployed and enables prediction of the shape of an object through the 3D pressure map.